Utilizing calcined agricultural biomass for the geopolymer stabilization of demolition wastes - Tung Doan; Arul Arulrajah; Annan Zhou; Suksun Horpibulsuk (Results in Engineering)
There is a growing need for alternative low carbon construction materials due to recent demand in road development. Traditional methods of building road pavement using virgin aggregates and cement have caused significant strain on the environments with high carbon output. As by-products of agricultural industry, rice hush ash (RHA) and bagasse ash (BA) were both investigated as novel replacement binders for pavement base applications. Various geotechnical tests were adopted to evaluate the strength performance of the new geopolymer binders in stabilizing demolitions wastes (C&D) including compaction tests, repeated triaxial loading tests (RLT), and unconfined compressive strength tests (UCS). Demolition wastes such as recycled concrete (RCA), crushed brick (CB), and reclaimed asphalt (RAP) were selected to be the main aggregates of the study. Laboratory calcination at 700 °C was implemented for RHA and BA production. Outcomes from this study showed significant strength development of RHA and BA geopolymer mixtures when combined with RCA at 10 % ratio while RAP could not attain sufficient strength development at 10 % precursor ratio due to poor gradation. In contrast, all CB mixtures delivered low strength outcomes at 7 days and 20 °C curing condition. Resilient modulus (Mr) results indicated stronger strain recovery behavior for RHA geopolymer mixtures than BA in general. Overall, both RHA and BA geopolymer were found to be suitable for pavement base applications when combined with RCA aggregates at 10 % precursor ratio in standard conditions, indicating great potential in replacing cement as the main binder for road pavement construction.